Isolated Complex Dorsal Dislocation of the Middle Finger Metacarpophalangeal Joint - H P Madhusudan; Anil Kumar Agarwal; S Raja Sabapathy (Indian Journal of Plastic Surgery)
Complex dislocations of the metacarpophalangeal joints are rare injuries. When they, occur, they are relatively common in the thumb, index and little fingers. Isolated complex dislocation of the metacarpophalangeal jont of the middle finger is extremely rare because of the inherent anatomical stability in that joint. We are reporting a case of isolated complex dorsal dislocation of the middle finger.